Hardening material and preparation method thereof and application in preparing explosion-proof hardening film
By reducing the silicon hydroxyl composition and using surface-treated nanoparticles in the hardened material of the explosion-proof hardened film, the problems of high cleaning and low reworkability during rework of the explosion-proof hardened film are solved, achieving more efficient reworking and cost savings.
Patent Information
- Application Number
- CN202411961280.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-01
AI Technical Summary
When reworking, the existing explosion-proof hardened films have a condensation reaction between the silicon hydroxyl group in the hardened coating and the silicon oxygen bond of OCA, which leads to high difficulty in cleaning, long time, low reworkability, and the uncleaned OCA can further lead to low rework yield.
By reducing the silicon hydroxyl composition in the hardened coating liquid formula of the hardened material, the surface-treated nanoparticles are used to reduce the reactivity with OCA, thereby improving reworkability.
Removal of OCA on the surface of the explosion-proof hardened film is easier to remove, improve rework efficiency, save costs, and improve adhesion and wear resistance of the hardened coating.
Smart Images

Figure CN119736014A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of optical films, and in particular to a hardening material and a preparation method thereof, and application thereof in the preparation of explosion-proof hardening films. Background Art
[0002] With the improvement of living standards, people pay more and more attention to safe travel, and ordinary car glass films can no longer meet the safety needs. In addition to all the functions of ordinary glass films, car explosion-proof hardened films also have the function of car glass explosion-proof. When the car is hit by a violent external force, it can improve the safety level of the car and minimize the possibility of car glass breaking, thereby ensuring the safety of passengers and reducing the secondary damage caused to people by the vehicle in the event of an accident.
[0003] At present, in the actual assembly process of explosion-proof hardened film, there will be a certain amount of defective products (impurities, bubbles and other problems), and rework is required at this time. The OCA is heated and then the glue layer is cut with a fishing line thinner than the glue layer, and then the residual OCA on the surface of the explosion-proof hardened film is cleaned for secondary processing. However, when cleaning the OCA on the surface of the explosion-proof hardened film, in order to improve the surface hardness of the hardened coating on the surface of the existing explosion-proof hardened film, silica nanoparticles are added to the hardened coating. After plasma treatment, the silica nanoparticles will produce silanols, which will react with the silicon oxygen bonds in the OCA to form chemical bonds, thereby generating a strong chemical bonding force between the two, resulting in great difficulty in cleaning, long cleaning time, low reworkability, and incompletely cleaned OCA can further lead to low rework yield.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] One of the purposes of the present invention is to provide a hardening material to at least solve one of the technical problems existing in the prior art. The hardening material provided by the present invention reduces the silanol component in the hardening coating liquid formula, reduces the reactivity with OCA during rework, thereby improving reworkability and saving costs.
[0006] A second object of the present invention is to provide a method for preparing a hardened material.
[0007] The third object of the present invention is to provide an application of the hardening material or the preparation method in the preparation of explosion-proof hardened film.
[0008] A fourth object of the present invention is to provide an explosion-proof hardened film.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0010] In a first aspect, the present invention provides a hardening material, comprising the following components: acrylate, photoinitiator, leveling agent, solvent and optional nanomaterial;
[0011] Wherein, the nanomaterial includes surface-treated nanoparticles.
[0012] Furthermore, the hardening material comprises the following components by weight:
[0013] 27-50 parts of acrylate, 0.3-3.0 parts of photoinitiator, 0.1-5.0 parts of leveling agent, 0-5 parts of nano material and 37.0-72.6 parts of organic solvent.
[0014] Furthermore, the nanomaterial includes nanoparticles treated with a silane coupling agent;
[0015] Preferably, the nanoparticles include at least one of aluminum oxide, silicon dioxide, titanium dioxide and zirconium dioxide;
[0016] Preferably, the silane coupling agent includes at least one of 3-aminopropyltriethoxysilane (KH550), γ-glycidyloxypropyltrimethoxysilane (KH560) and γ-(methacryloyloxy)propyltrimethoxysilane (KH570);
[0017] Preferably, the mass ratio of the silane coupling agent to the nanoparticles is 0.1-0.3;
[0018] Preferably, the D90 particle size of the nanoparticles treated with the silane coupling agent is 20-100 nm, preferably 20-50 nm.
[0019] Further, the acrylate includes at least one of epoxy acrylate resin, polyurethane acrylate resin and polyester acrylate resin;
[0020] Preferably, the photoinitiator comprises at least one of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexylphenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, benzophenone, 4-methylbenzophenone and 2,4,6-trimethylbenzophenone;
[0021] Preferably, the leveling agent comprises an acrylate leveling agent;
[0022] Preferably, the organic solvent comprises at least one of ethyl acetate, butyl acetate, toluene, xylene, propylene glycol methyl ether, dipropylene glycol methyl ether, acetone, butanone, cyclohexanone, methyl isobutyl ketone, isopropyl alcohol and isobutyl alcohol.
[0023] In a second aspect, the present invention provides a method for preparing the hardened material, comprising the following steps:
[0024] The hardened material is prepared by mixing formulated amounts of acrylate, photoinitiator, leveling agent, solvent and optional nanomaterial.
[0025] Furthermore, the mixing speed is 300-800 r / min, and the mixing time is 10-40 min;
[0026] Preferably, the nanoparticles treated with a silane coupling agent are prepared by the following steps:
[0027] Nanoparticles are added to a mixed solution of anhydrous ethanol and water, the reaction temperature is 60-80°C, a silane coupling agent is added, and the pH value of the system is adjusted to 4 with an acid agent to obtain a nanoparticle suspension. The nanoparticle suspension is then filtered, and the filter cake is dried and ground to obtain the nanoparticles treated with the silane coupling agent.
[0028] In a third aspect, the present invention provides an application of the hardening material or the preparation method in preparing an explosion-proof hardening film.
[0029] In a fourth aspect, the present invention provides an explosion-proof hardened film, comprising a substrate layer and a hardened coating layer;
[0030] forming the hardened coating layer by applying a hardened coating liquid to the surface of the substrate layer;
[0031] The hardening coating liquid is prepared by using the hardening material or the preparation method.
[0032] Furthermore, the substrate layer includes at least one of polyethylene terephthalate substrate, cellulose triacetate, polymethyl methacrylate and SRF.
[0033] Furthermore, the explosion-proof hardened film is prepared by the following steps:
[0034] The base layer to which the hardened coating liquid is applied is dried and cured in sequence to obtain the explosion-proof hardened film;
[0035] Preferably, the drying temperature is 80-100°C, and the drying time is 2-4 minutes;
[0036] Preferably, the curing is performed by ultraviolet light irradiation.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] The hardening material provided by the present invention can reduce the surface silanol content by adopting surface-treated nanoparticles, thereby reducing the chemical bonding force between OCA and the surface of the hardening material, and then the OCA remaining on the surface of the explosion-proof hardening film can be more easily removed during rework, thereby improving the rework efficiency and saving costs; in addition, when no nanomaterial is added to the hardening material component, there will be no condensation reaction between the silanol on the surface of the hardened coating and the silicon-oxygen bonds of OCA, thereby improving the reworkability. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0040] Figure 1 This is a microscopic morphology of the explosion-proof hardened film after rework and cleaning provided in Application Example 1 of the present invention;
[0041] Figure 2 This is a microscopic morphology of the explosion-proof hardened film after rework and cleaning provided in Application Example 2 of the present invention;
[0042] Figure 3 This is a microscopic morphology of the explosion-proof hardened film after rework and cleaning provided in Application Example 3 of the present invention;
[0043] Figure 4 This is a microscopic morphology of the explosion-proof hardened film after rework and cleaning provided in Application Example 7 of the present invention;
[0044] Figure 5 A schematic diagram of the structure of the explosion-proof hardened film provided by the present invention;
[0045] Figure 6 This is the microscopic morphology of the explosion-proof hardened film after rework and cleaning provided in comparative application example 1.
[0046] Icon: 1-base material layer; 2-explosion-proof hardened layer. DETAILED DESCRIPTION
[0047] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.
[0048] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] The first aspect of the present invention provides a hardening material, comprising the following components: acrylate, photoinitiator, leveling agent, solvent and optional nanomaterial; wherein the nanomaterial comprises surface-treated nanoparticles.
[0050] The hardening material provided by the present invention can reduce the surface silanol content by adopting surface-treated nanoparticles, thereby reducing the chemical bonding force between OCA and the surface of the hardening material, and then the OCA remaining on the surface of the explosion-proof hardening film can be more easily removed during rework, thereby improving the rework efficiency and saving costs; in addition, when no nanomaterial is added to the hardening material component, there will be no condensation reaction between the silanol on the surface of the hardened coating and the silicon-oxygen bonds of OCA, thereby improving the reworkability.
[0051] In some preferred embodiments, the hardening material comprises the following components by weight:
[0052] 27-50 parts of acrylate, 0.3-3.0 parts of photoinitiator, 0.1-5.0 parts of leveling agent, 0-5 parts of nano material and 37.0-72.6 parts of organic solvent.
[0053] Based on 100 parts of the total weight of the hardening material, the amount of acrylate added is 27 to 50 parts, for example, 27 parts, 30 parts, 35 parts, 40 parts, 42 parts, 50 parts, etc.;
[0054] Based on 100 parts of the total weight of the hardening material, the amount of the photoinitiator added is 0.3 to 3.0 parts, for example, 0.3 parts, 1 part, 1.2 parts, 1.8 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, etc.;
[0055] Based on 100 parts of the total mass of the hardening material, the amount of the leveling agent added is 0.1 to 5.0 parts, for example, 0.1 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, etc.;
[0056] Based on 100 parts of the total mass of the hardening material, the amount of the nano material added is 0-5 parts, for example, 0 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, etc.
[0057] Based on 100 parts of the total mass of the hardening material, the added amount of the organic solvent is 37.0 to 72.6 parts.
[0058] In the present invention, the mass fraction of the nanomaterial in the hardening material can be 0, the hardening material does not contain silicon dioxide nanoparticles, and no silanol group on the surface of the hardened coating will undergo condensation reaction with the silicon oxygen bond of OCA, thereby improving the reworkability.
[0059] In some preferred embodiments, the nanomaterial includes nanoparticles treated with a silane coupling agent;
[0060] Specifically, in the present invention, nanoparticles are treated with a silane coupling agent to obtain the nanomaterial.
[0061] Preferably, the nanoparticles include at least one of aluminum oxide, silicon dioxide, titanium dioxide and zirconium dioxide;
[0062] In the present invention, the nanomaterial is preferably silicon dioxide treated with a silane coupling agent. On the one hand, the surface activity of silicon dioxide nanoparticles is relatively low, and on the other hand, the surface treated silicon dioxide nanoparticles can further reduce the surface silanol content, thereby reducing the chemical bonding force between OCA and the surface of the hardened coating, and then the residual OCA on the surface of the explosion-proof hardened film can be more easily removed during rework, thereby improving rework efficiency and saving costs.
[0063] Preferably, the silane coupling agent includes at least one of 3-aminopropyltriethoxysilane (KH 550), γ-glycidyloxypropyltrimethoxysilane (KH 560), and γ-(methacryloyloxy)propyltrimethoxysilane (KH 570);
[0064] Preferably, the D90 particle size of the nanoparticles treated with the silane coupling agent is 20-100 nm, preferably 20-50 nm.
[0065] In some preferred embodiments, the acrylate includes at least one of epoxy acrylate resin, polyurethane acrylate resin and polyester acrylate resin;
[0066] The present invention further uses polyurethane-modified acrylic resin to enhance the adhesion between the hardened coating and the substrate layer, thereby preventing the coating from falling off during use.
[0067] Preferably, the photoinitiator comprises at least one of 2-hydroxy-2-methyl-1-phenylpropanone (1173), 1-hydroxycyclohexylphenyl ketone (184), 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone (907), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (photoinitiator TPO), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone (369), phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (819), benzophenone (BP), 4-methylbenzophenone and 2,4,6-trimethylbenzophenone.
[0068] Preferably, the leveling agent comprises an acrylate leveling agent;
[0069] Preferably, the organic solvent comprises at least one of ethyl acetate, butyl acetate, toluene, xylene, propylene glycol methyl ether, dipropylene glycol methyl ether, acetone, butanone, cyclohexanone, methyl isobutyl ketone, isopropyl alcohol and isobutyl alcohol.
[0070] A second aspect of the present invention provides a method for preparing the hardened material, comprising the following steps:
[0071] The hardened material is prepared by mixing formulated amounts of acrylate, photoinitiator, leveling agent, solvent and optional nanomaterial.
[0072] In some preferred embodiments, the stirring speed of the mixing is 300-800 r / min, for example, 300 r / min, 400 r / min, 500 r / min, 600 r / min, 700 r / min, 800 r / min, etc.; the mixing time is 10-40 min, for example, 10 min, 20 min, 30 min, 40 min, etc.;
[0073] Preferably, the nanoparticles treated with a silane coupling agent are prepared by the following steps:
[0074] A certain amount of nanoparticles is added to a mixed solution of anhydrous ethanol / water (volume ratio of 3:1), and the nanoparticles are fully dispersed under a high-speed shear of 4000 r / min. The shear rate is adjusted to 2000 r / min, the reaction temperature is 60-80°C, a silane coupling agent is added, and the mass ratio of the silane coupling agent to the nanoparticles is 0.1-0.3. The pH value of the system is adjusted to 4 with an oxalic acid solution, and the reaction is carried out for 90 minutes. The nano-silicon dioxide suspension is filtered, and the filter cake is dried and ground to obtain the nanoparticles treated with the silane coupling agent.
[0075] A third aspect of the present invention provides an application of the hardening material or the preparation method in preparing an explosion-proof hardened film.
[0076] In order to improve the reworkability of the explosion-proof hardened film during rework, the hardening material formula is optimized during the manufacturing process of the explosion-proof hardened film, and the silanol components in the hardening materials of the prior art are removed or reduced. Specifically, the hardening material provided by the present invention is prepared into a hardening coating liquid, and then into a hardening coating, which can prevent the siloxane bonds in the OCA from condensing with the silanols on the surface of the hardening coating, thereby reducing the difficulty of cleaning the OCA on the surface of the explosion-proof hardened film and improving the reworkability; at the same time, the hardened explosion-proof film also has good performance in optics, adhesion, hardness and wear resistance.
[0077] The fourth aspect of the present invention provides an explosion-proof hardened film, comprising a substrate layer 1 and a hardened coating layer; the hardened coating layer is formed by applying a hardening coating liquid to the surface of the substrate layer; the hardening coating liquid is prepared using the hardening material or the preparation method.
[0078] In the present invention, Figure 5 As shown, the hardened coating is an explosion-proof hardened layer 2 , and the explosion-proof hardened film includes a base material layer 1 and an explosion-proof hardened layer 2 .
[0079] The explosion-proof hardened film provided by the present invention is formed by selecting and configuring the above-mentioned hardening coating liquid, and preparing a hardened layer on the surface of the substrate layer. On the one hand, the hardened layer and the substrate layer have good adhesion, hardness and wear resistance. On the other hand, when the explosion-proof hardened film is reworked, the hardened coating on the surface of the hardened film does not contain or contains a small amount of silanol components, thereby avoiding condensation reaction between silanol and OCA, thereby reducing the chemical bonding force between OCA and the surface of the hardened coating, ensuring adhesion while improving the reworkability of the explosion-proof hardened film, greatly reducing the rework cost, and at the same time, the OCA remaining on the surface of the explosion-proof hardened film can be more easily removed during rework, thereby improving rework efficiency and saving costs.
[0080] In some preferred embodiments, the substrate layer includes at least one of polyethylene terephthalate substrate (PET), triacetyl cellulose (TAC), polymethyl methacrylate (PMMA) and SRF (TOYOBO Super Retardation Film).
[0081] In some preferred embodiments, the explosion-proof hardened film is prepared by the following steps:
[0082] The base layer to which the hardened coating liquid is applied is dried and cured in sequence to obtain the explosion-proof hardened film;
[0083] Preferably, the drying temperature is 80-100°C, and the drying time is 2-4 minutes;
[0084] Preferably, the curing is performed by ultraviolet light irradiation.
[0085] In the present invention, the preparation process of the explosion-proof hardened film is specifically as follows: (1) using a wet coating method to evenly coat the hardened film coating liquid on the surface of the substrate; (2) after being treated in an oven at 80-100°C for 2-4 minutes, it is cured by ultraviolet light to obtain an explosion-proof hardened film.
[0086] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.
[0087] It should be noted that the D90 particle size of the nanoparticles treated with the silane coupling agent selected in the following embodiments of the present invention is 20-50 nm.
[0088] Example 1
[0089] This embodiment provides a hardening material, which includes the following components by weight:
[0090] 40 parts of polyurethane acrylic resin, 0.4 parts of photoinitiator 1-hydroxycyclohexyl phenyl ketone (184) (184), 2 parts of acrylic leveling agent (BYK-358N) and the balance of butyl acetate solvent.
[0091] Example 2
[0092] This embodiment provides a hardening material, which differs from the embodiment 1 in that: 2 portions of nanomaterial are added;
[0093] The nano material is silicon dioxide treated with a silane coupling agent, and the weight ratio of the silane coupling agent to silicon dioxide is 0.2; the other components are consistent with those in Example 1.
[0094] Example 3
[0095] This embodiment provides a hardening material, which differs from Embodiment 2 in that the mass ratio of the silane coupling agent to silicon dioxide is 0.1; and the other components are consistent with those in Embodiment 2.
[0096] Example 4
[0097] This embodiment provides a hardening material, which differs from Embodiment 2 in that the mass ratio of silane coupling agent to silicon dioxide is 0.3; and the other components are consistent with Embodiment 2.
[0098] Example 5
[0099] This embodiment provides a hardening material, which differs from Embodiment 2 in that the mass ratio of silane coupling agent to silicon dioxide is 0.03; and the other components are consistent with those in Embodiment 2.
[0100] Example 6
[0101] This embodiment provides a hardening material, which differs from Embodiment 2 in that the mass ratio of the silane coupling agent to silicon dioxide is 0.5; and the other components are consistent with those in Embodiment 2.
[0102] Example 7
[0103] This embodiment provides a hardening material, which is different from Embodiment 2 in that:
[0104] 27 parts of polyurethane acrylic resin, 3 parts of photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone (1173), 0.1 parts of acrylic leveling agent (BYK-358N), 5 parts of nanomaterial (the nanomaterial is titanium dioxide treated with a silane coupling agent) and the balance of dipropylene glycol methyl ether solvent;
[0105] The remaining components are consistent with those in Example 2.
[0106] Example 8
[0107] This embodiment provides a hardening material, which is different from Embodiment 2 in that:
[0108] 50 parts of polyurethane acrylic resin, 0.3 parts of photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone (1173), 5 parts of acrylic leveling agent (BYK-358N), 0.5 parts of nanomaterial (the nanomaterial is titanium dioxide treated with a silane coupling agent) and the balance of dipropylene glycol methyl ether solvent;
[0109] The remaining components are consistent with those in Example 2.
[0110] Example 9
[0111] This embodiment provides a hardening material, which is different from Embodiment 2 in that:
[0112] 26 parts of polyurethane acrylic resin, 3.5 parts of photoinitiator 1-hydroxycyclohexyl phenyl ketone (184) (184), 0.05 parts of acrylic leveling agent (BYK-358N), 5.5 parts of nanomaterials and the balance of butyl acetate solvent;
[0113] The remaining components are consistent with those in Example 2.
[0114] Example 10
[0115] This embodiment provides a hardening material, which is different from Embodiment 2 in that:
[0116] 51 parts of polyurethane acrylic resin, 0.2 parts of photoinitiator 1-hydroxycyclohexyl phenyl ketone (184) (184), 5.5 parts of acrylic leveling agent (BYK-358N), 0.5 parts of nanomaterial and the balance of butyl acetate solvent;
[0117] The remaining components are consistent with those in Example 2.
[0118] Examples 11-20
[0119] Examples 11-20 provide a method for preparing a hardened material, using the hardened materials in Examples 1-10 respectively.
[0120] Among them, the preparation method of the hardening material of Example 11 is prepared using the hardening material of Example 1, and specifically includes the following steps: the raw material components of Example 1 are placed into the barrel according to the above-mentioned weight ratio for mixing, the stirring speed is 550r / min, and the dispersion time is 25min; thereafter, the mixed hardening coating liquid is sealed and stored, and left to stand for use.
[0121] The method for preparing the hardened material of Example 12 is prepared by using the hardened material of Example 2, and specifically comprises the following steps:
[0122] (a) Preparation of nanomaterials (silicon dioxide treated with a silane coupling agent): A certain amount of nano-silicon dioxide was added to a mixed solution of anhydrous ethanol / water (volume ratio of 3:1), and the mixture was fully dispersed under high-speed shearing at 4000 r / min. The shear rate was adjusted to 2000 r / min, and the reaction temperature was 70°C. Silane coupling agent KH570 was added, and the mass ratio of silane coupling agent to nano-silicon dioxide was 1:5 (0.2). The pH value of the system was adjusted to 4 with oxalic acid solution, and the reaction was carried out for 90 minutes. The nano-silicon dioxide suspension was filtered, dried, and ground to obtain the nanoparticles treated with the silane coupling agent.
[0123] (b) The raw material components of Example 2 were placed in a barrel according to the above weight ratio for mixing, with a stirring speed of 550 r / min and a dispersion time of 25 min. Afterwards, the mixed hardened coating liquid was sealed and stored and allowed to stand for use.
[0124] The method for preparing the hardened material of Example 13 is prepared by using the hardened material of Example 3, and specifically comprises the following steps:
[0125] (a) The nanomaterial formula of Example 3 was used to prepare a nanomaterial (silicon dioxide treated with a silane coupling agent). The preparation process was the same as that of Example 12, except that the reaction temperature was adjusted to 60° C.;
[0126] (b) The raw material components of Example 3 were placed in a barrel according to the above weight ratio for mixing, with a stirring speed of 550 r / min and a dispersion time of 25 min; thereafter, the mixed hardened coating liquid was sealed and stored and allowed to stand for use.
[0127] The method for preparing the hardened material of Example 14 is prepared by using the hardened material of Example 4, and specifically comprises the following steps:
[0128] (a) The nanomaterial formula of Example 4 was used to prepare a nanomaterial (silicon dioxide treated with a silane coupling agent). The preparation process was the same as that of Example 12, except that the reaction temperature was adjusted to 80° C.;
[0129] (b) The raw material components of Example 4 were placed into a barrel according to the above weight ratio for mixing, with a stirring speed of 550 r / min and a dispersion time of 25 min; thereafter, the mixed hardened coating liquid was sealed and stored and allowed to stand for use.
[0130] Among them, the preparation methods of the hardening materials of Examples 15-16 are prepared using the hardening materials of Examples 5-6 respectively, and the preparation methods are consistent with Example 12.
[0131] The method for preparing the hardened material of Example 17 is prepared by using the hardened material of Example 7, and the difference from Example 12 is:
[0132] (a) In the preparation process of the nanomaterial (titanium dioxide treated with a silane coupling agent), the nanoparticles are selected from titanium dioxide;
[0133] (b) The raw material components of Example 7 were placed in a barrel according to the above weight ratio for mixing, the stirring speed was 300 r / min, and the dispersion time was 40 min; then, the mixed hardened coating liquid was sealed and stored, and left to stand for use; the remaining steps were the same as those of Example 12;
[0134] The remaining steps are consistent with Example 12.
[0135] The difference between the method for preparing the hardened material of Example 18 and the preparation of the hardened material of Example 8 and Example 12 is:
[0136] (a) In the preparation process of the nanomaterial (titanium dioxide treated with a silane coupling agent), the nanoparticles are selected from titanium dioxide;
[0137] (b) The raw material components of Example 8 were placed in a barrel according to the above weight ratio for mixing, the stirring speed was 800 r / min, and the dispersion time was 10 min; then, the mixed hardened coating liquid was sealed and stored, and left to stand for use; the remaining steps were the same as those of Example 12;
[0138] The remaining steps are consistent with Example 12.
[0139] Among them, the preparation methods of the hardened materials of Examples 19-20 are prepared using the hardened materials of Examples 9-10 respectively, and the preparation process is consistent with that of Example 12.
[0140] Application Examples 1-10
[0141] Application Examples 1-10 provide an explosion-proof hardened film, which includes a substrate layer and a hardened coating liquid coated on the surface of the substrate layer. The hardened coating liquids prepared in Examples 11-20 are used for preparation, and specifically include the following steps:
[0142] Using the wet coating method, the hardened coating liquids prepared in Examples 11-20 were evenly coated on the surface of the substrate (PET was selected as the substrate) through a wire rod / anilox roller and then dried in a 90°C oven for 3 minutes. After the solvent was completely evaporated, it was cured by ultraviolet light to form a hardened coating, thereby obtaining an explosion-proof hardened film.
[0143] Application Example 11
[0144] This application example provides an explosion-proof hardened film, which is different from application example 2 in that:
[0145] The substrate is polymethyl methacrylate (PMMA);
[0146] After being treated in an oven at 80°C for 4 minutes, the film was cured by ultraviolet light to obtain an explosion-proof hardened film. The remaining steps were consistent with those in Application Example 2.
[0147] Application Example 12
[0148] This application example provides an explosion-proof hardened film, which is different from application example 2 in that:
[0149] The substrate is SRF;
[0150] After being treated in an oven at 100°C for 2 minutes, the film was cured by ultraviolet light to obtain an explosion-proof hardened film. The remaining steps were consistent with those in Application Example 2.
[0151] Comparative Example 1
[0152] This comparative example provides a hardening material, which comprises the following components by weight:
[0153] Polyurethane acrylic resin: 40 parts; Photoinitiator 184: 0.4 parts; Acrylic leveling agent BYK-358N: 2 parts; Silicone 1124: 3 parts; Butyl acetate solvent: 54.6 parts.
[0154] Comparative Example 2
[0155] This comparative example provides a hardening material, which is different from Example 2 in that it does not contain a photoinitiator.
[0156] Comparative Example 3
[0157] This comparative example provides a hardening material, which is different from Example 2 in that it does not contain a leveling agent.
[0158] Comparative Examples 4-6
[0159] This comparative example provides a method for preparing a hardening material, using the hardening materials of comparative examples 1-3 respectively, and the preparation steps are consistent with those of Example 12. Among them, since the hardening material of comparative example 3 does not contain nanomaterials, the preparation steps of comparative example 4 do not need to prepare nanomaterials.
[0160] Comparative Application Examples 1-3
[0161] This application example provides an explosion-proof hardened film, which is prepared using the hardened materials prepared in Comparative Examples 4-6, respectively, and the preparation method is consistent with that of Application Example 2.
[0162] Test Case
[0163] Test samples: explosion-proof hardened films prepared by using application examples 1-12 and explosion-proof hardened films prepared by using comparative application examples 1-3.
[0164] Test method:
[0165] (1) Coating adhesion
[0166] Referring to the standard GB / T 9286, the coating surface of the explosion-proof hardened film was cut into 100 cross-section lines with a cutter, wherein the size of each cross-section line was 1mm×1mm, and then 3M-600 professional test tape (3M Company) was adhered to the cross-section hard coating surface with a force of 2.0Kg. After 3min, the 3M tape was peeled off from the surface at an angle of 90°. The coating adhesion was evaluated by counting the number of cross-section lines of the hard coating left on the support, and was divided into 5 levels from low to high: 1B, 2B, 3B, 4B and 5B.
[0167] (2) Reworkability
[0168] The coating surface of the explosion-proof hardened film is bonded with OCA, and then degassing treatment is carried out at a temperature of 50°C, a pressure of 0.2Mpa, and a time of 300min. Subsequently, the OCA is heated to 60°C and the adhesive layer is cut with a fishing line. The residual OCA on the surface of the hardened coating is wiped with a dust-free cloth and alcohol; an evaluation is conducted based on the residual OCA, which is divided into three levels from less to more: none, slight, and severe.
[0169] The test results are shown in Table 1.
[0170] Table 1
[0171] sample Reworkability Adhesion Application Example 1 none 5B Application Example 2 none 5B Application Example 3 slight 5B Application Example 4 slight 5B Application Example 5 serious 5B Application Example 6 slight 5B Application Example 7 slight 5B Application Example 8 none 4B Application Example 9 serious 3B Application Example 10 slight 4B Application Example 11 none 5B Application Example 12 none 5B Comparative application example 1 serious 5B Comparative Application Example 2 none 2B Comparative Application Example 3 none 3B
[0172] It can be seen from the data in Table 1 that after the nano-silica particles are treated with a silane coupling agent, the surface silanol components are effectively reduced, thereby preventing the condensation reaction between the silanol and OCA, thereby reducing the chemical bonding force between the OCA and the surface of the hardened coating and improving the reworkability; it can be seen from Application Examples 11 and 12 that the hardened coating provided in the present application has good adhesion to both the polymethyl methacrylate (PMMA) substrate and the SRF substrate.
[0173] in, Figure 1 This is a microscopic morphology of the explosion-proof hardened film after rework and cleaning provided in Application Example 1 of the present invention. Figure 2 This is a microscopic morphology of the explosion-proof hardened film after rework and cleaning provided in Application Example 2 of the present invention. Figure 3 This is a microscopic morphology of the explosion-proof hardened film after rework and cleaning provided in Application Example 3 of the present invention. Figure 4 This is a microscopic morphology of the explosion-proof hardened film after rework and cleaning provided in Application Example 7 of the present invention. Figure 6 The microscopic morphology of the explosion-proof hardened film after rework and cleaning provided in comparative application example 1. It can be seen that after rework and cleaning, there is no residual OCA on the surface of the explosion-proof hardened film of the application example of the present invention, while there is more residual OCA on the surface of the comparative application example.
[0174] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A hardening material, characterized in that: The invention comprises the following components: acrylate, photoinitiator, leveling agent, solvent and optional nanomaterial; Wherein, the nanomaterial includes surface-treated nanoparticles.
2. The hardening material according to claim 1, characterized in that The hardening material comprises the following components by weight: 27-50 parts of acrylate, 0.3-3.0 parts of photoinitiator, 0.1-5.0 parts of leveling agent, 0-5 parts of nano material and 37.0-72.6 parts of organic solvent.
3. The hardening material according to claim 1, characterized in that The nano material includes nano particles treated with a silane coupling agent; Preferably, the nanoparticles include at least one of aluminum oxide, silicon dioxide, titanium dioxide and zirconium dioxide; Preferably, the silane coupling agent includes at least one of 3-aminopropyltriethoxysilane (KH550), γ-glycidyloxypropyltrimethoxysilane (KH560) and γ-(methacryloyloxy)propyltrimethoxysilane (KH570); Preferably, the mass ratio of the silane coupling agent to the nanoparticles is 0.1-0.3; Preferably, the D90 particle size of the nanoparticles treated with the silane coupling agent is 20-100 nm, preferably 20-50 nm.
4. The hardening material according to claim 1, characterized in that The acrylate comprises at least one of epoxy acrylate resin, polyurethane acrylate resin and polyester acrylate resin; Preferably, the photoinitiator comprises at least one of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexylphenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, benzophenone, 4-methylbenzophenone and 2,4,6-trimethylbenzophenone; Preferably, the leveling agent comprises an acrylate leveling agent; Preferably, the organic solvent comprises at least one of ethyl acetate, butyl acetate, toluene, xylene, propylene glycol methyl ether, dipropylene glycol methyl ether, acetone, butanone, cyclohexanone, methyl isobutyl ketone, isopropyl alcohol and isobutyl alcohol.
5. The method for preparing a hardened material according to any one of claims 1 to 4, characterized in that: The following steps are involved: The hardened material is prepared by mixing formulated amounts of acrylate, photoinitiator, leveling agent, solvent and optional nanomaterial.
6. The preparation method according to claim 5, characterized in that: The mixing speed is 300-800 r / min, and the mixing time is 10-40 min; Preferably, the nanoparticles treated with a silane coupling agent are prepared by the following steps: Nanoparticles are added to a mixed solution of anhydrous ethanol and water, the reaction temperature is 60-80°C, a silane coupling agent is added, and the pH value of the system is adjusted to 4 with an acid agent to obtain a nanoparticle suspension. The nanoparticle suspension is then filtered, and the filter cake is dried and ground to obtain the nanoparticles treated with the silane coupling agent.
7. Use of the hardening material according to any one of claims 1 to 4 or the preparation method according to claim 5 or 6 in preparing explosion-proof hardened films.
8. An explosion-proof hardened film, characterized in that: including a substrate layer and a hardening coating layer; forming the hardened coating layer by applying a hardening coating liquid to the surface of the substrate layer; The hardening coating liquid is prepared by using the hardening material according to any one of claims 1 to 4 or the preparation method according to claim 5 or 6.
9. The explosion-proof hardened film according to claim 8, characterized in that: The substrate layer includes at least one of a polyethylene terephthalate substrate, cellulose triacetate, polymethyl methacrylate, and SRF.
10. The explosion-proof hardened film according to claim 8, characterized in that: The explosion-proof hardened film is prepared by the following steps: The base layer to which the hardened coating liquid is applied is dried and cured in sequence to obtain the explosion-proof hardened film; Preferably, the drying temperature is 80-100°C, and the drying time is 2-4 minutes; Preferably, the curing is performed by ultraviolet light irradiation.